2020
DOI: 10.1063/5.0007511
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of methane hydrate under pressures up to 134 GPa

Abstract: High-pressure experiments were performed to understand the structural evolution of methane hydrate (MH) up to 134 GPa using x-ray powder diffraction (XRD) and Raman spectroscopy with diamond anvil cells. XRD revealed the distinct changes in the diffraction lines of MH owing to phase transition from a guest-ordered state phase [MH-III(GOS)] to a new high-pressure phase (MH-IV) at 33.8–57.7 GPa. MH-IV was found to be stable up to at least 134 GPa without decomposition into solid methane and high-pressure ices. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The state changes such as phase transition, melting, and solid–solid decomposition of the MH sample can be detected by measuring the frequency of C–H vibration modes of the sample and the pressure in the sample chamber because the C–H vibration modes of methane molecules are very sensitive to the surrounding conditions. [ 10,16,22–26 ] Therefore, in this study, we measured symmetric and antisymmetric stretching vibration modes, ν 1 and ν 3 , respectively, of C–H vibration modes of methane molecules because these two modes show a relatively large pressure dependence, and high‐intensity Raman signals can be obtained in a few minutes under high P–T. [ 10 ]…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The state changes such as phase transition, melting, and solid–solid decomposition of the MH sample can be detected by measuring the frequency of C–H vibration modes of the sample and the pressure in the sample chamber because the C–H vibration modes of methane molecules are very sensitive to the surrounding conditions. [ 10,16,22–26 ] Therefore, in this study, we measured symmetric and antisymmetric stretching vibration modes, ν 1 and ν 3 , respectively, of C–H vibration modes of methane molecules because these two modes show a relatively large pressure dependence, and high‐intensity Raman signals can be obtained in a few minutes under high P–T. [ 10 ]…”
Section: Methodsmentioning
confidence: 99%
“…The fundamental structure of MH-III is retained up to at least 134 GPa via some phase transitions occurring at 15 GPa and at 34 GPa. [6][7][8][9][10][11] On the basis of its high-pressure stability, MH is thought to be ubiquitous in space, and it is an important constituent of outer icy planets and their moons. Recent experimental and theoretical studies suggested that in Saturn's largest moon Titan, MH exists in the icy mantle as well as in the icy crust, which is an essential source of atmospheric methane.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations